Multipath fabrication of hierarchical CuAl layered double hydroxide/carbon fiber composites for the degradation of ammonia nitrogen. (15th August 2018) - Peng, Xiaoming; Wang, Min; Hu, Fengping; Qiu, Fengxian; Zhang, Tao; Dai, Hongling; Cao, Zan
Abstract: In this work, a series of flower-like CuAl layered double hydroxides (LDHs) and hierarchical CuAl/carbon fiber-LDH (CuAl/CF-LDH) materials were synthesized, and these materials were used as catalysts for the degradation of ammonia nitrogen from simulated wastewater. The morphologies and structures of the materials were characterized using scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy (RS), X-ray diffraction (XRD), and the Brunauer-Emmett-Teller (BET) technique. The effects of the catalyst and H2 O2 loading dosages, reaction temperature, pH, Cu/Al ratio of the samples, and contact time on the degradation process were investigated by degrading ammonia nitrogen under different conditions, and the possible degradation mechanism was discussed. CuAl/CF-LDH exhibited more effectively catalytically degradation of ammonia nitrogen than others as-prepared samples, and removal efficiency reached 99.7% under the optimized conditions. The reusing capability and stability of the materials were studied. Meanwhile, the versatility of the materials was investigated by testing their performance in the absorption of azo dye, the highest removal efficiency was found to be 99.28%. The prepared materials are promising for use as effective catalysts for the degradation of ammonia nitrogen from wastewater. Highlights: A series of flower-like CuAl-layered double hydroxide and hierarchical CuAl/CF-layered double hydroxide were synthesized. The as-prepared materials can maintained excellent reuse ability. The materials exhibited excellent adsorption and degradation property for ammonia nitrogen. The materials possess versatility for adsorption of dye.